Surface-Enhanced Raman Spectroscopy (SERS) for characterization SARS-CoV-2 - Javier Christian Ramirez-Perez; Daniele Durigo (Journal of Saudi Chemical Society)
We used SERS with silver nanoparticles (AgNPs) as the active substrate to develop a, simple, quick, and accurate method for the detection and characterization SARS-CoV-2 without the need for RNA isolation and purification. Inactivated SARS-CoV-2 was used. The SERS signals were more than 105 times enhanced than the normal Raman (NR) spectra. The SERS spectra of SARS-CoV-2 fingerprint revealed pronounced intensity signals of nucleic acids; aromatic amino acid side chains: 1007 cm−1 (Phe marker), 1095 cm−1 (CN and PO2− markers), 1580 cm−1 (Tyr, Trp markers). Vibrations of the protein main chain: 1144 cm−1 (CN and NH2 markers), 1221 cm−1 (CN and NH markers), 1270 cm−1 (NH2 marker), 1453 cm−1 (CHCH2 marker). All of these biomolecules could be adsorbed on the AgNPs surface's dense hot patches. The intensity of the SERS band varied with the concentration of SARS-CoV-2, with a virus detection limit of less than 103 vp/mL and RSDs of 20 %.